Personal Bankruptcy Law, Wealth and Entrepreneurship: Theory and Evidence from the Introduction of a "Fresh Start" - Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
A personal bankruptcy law that allows for a "fresh start" after bankruptcy reduces the individual risk involved in entrepreneurial activity. On the other hand, as risk shifts to creditors who recover less of their credit after a debtor's bankruptcy, lenders may charge higher interest rates or ration credit supply, which can hamper entrepreneurship. Both aspects of a more forgiving personal bankruptcy law are less relevant for wealthy potential. - entrepreneurs who still risk losing their wealth, but tend not to face higher interest rates because they provide collateral. This paper illustrates these effects in a model and tests the hypotheses derived by exploiting the introduction of a "fresh start" policy in Germany in 1999 as a natural experiment, based on representative household panel data. The results indicate that the insurance effect of a more forgiving personal bankruptcy law exceeds the interest effect and on balance encourages less wealthy individuals to enter into entrepreneurship.
Keywords: K35; G33; L26; 330; Personal bankruptcy law; insolvency; entrepreneurship; fresh start; Insolvenz; Unternehmer; Kreditgeschäft; Zins; Kreditrationierung; Kreditsicherung; Anreiz; Deutschland